2022
DOI: 10.9734/jpri/2022/v34i3b35392
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Alpha-Amylase and Alpha- Glucosidase Inhibitory Potential of Aqueous Seed Extract of Trigonella Foenum-Graecum and Moringa Oleifera - An In vitro Study

Abstract: Background: Trigonella foenum-graecum is one of the commonly used herbs in food. Moringa oleifera is a source of food, accommodation and conventional medicine for many peoples in the developing countriesThe seeds of both the plants were explored for antidiabetic potential. Methods: The current work was designed to probe the in vitro anti diabetic potential of the aqueous seed elicit of trigonella foenum- graceus and Moringa oleifera using the enzymes alpha amylase and alpha glucosidase.Both the extracts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 18 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…A study conducted by Prithiksha et al. ( 2022 ) tested the α‐glucosidase activity of aqueous fenugreek seed extract, and the results indicated that α‐glucosidase inhibition activity of extracts (100–500 μg/mL) ranged from 21% to 58% linearly. Moreover, Ganeshpurkar et al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A study conducted by Prithiksha et al. ( 2022 ) tested the α‐glucosidase activity of aqueous fenugreek seed extract, and the results indicated that α‐glucosidase inhibition activity of extracts (100–500 μg/mL) ranged from 21% to 58% linearly. Moreover, Ganeshpurkar et al.…”
Section: Resultsmentioning
confidence: 99%
“…Prithiksha et al (2022) tested the α-amylase activity of 80% aqueous fenugreek seed extract at different concentrations ranging from 100 to 500 μg/mL. Results depicted the linear relationship between concentrations and α-amylase inhibition as the % inhibition activity ranged from 30% at 100 μg/mL to 85% at 500 μg/mL Sunita (2020).…”
mentioning
confidence: 99%
See 1 more Smart Citation